Europa's plasma interaction with an inhomogeneous atmosphere: Development of Alfven winglets within the Alfven wings - Bloecker, Aljona; Saur, Joachim; Roth, Lorenz (AMER GEOPHYSICAL UNION, 2016)
We apply a three-dimensional magnetohydrodynamic (MHD) model to study the influence of inhomogeneities in Europa's atmosphere, as, for example, water vapor plumes, on Europa's plasma interaction with the Jovian magnetosphere. In our model we have included electromagnetic induction in a subsurface water ocean, collisions between ions and neutrals, plasma production and loss due to electron impact ionization, and dissociative recombination. We present a systematic study of the plasma interaction when a local inhomogeneity in the neutral density is present within a global sputtering generated atmosphere. We show that an inhomogeneity near the north or south pole affects the plasma interaction in a way that a pronounced north-south asymmetry is generated. We find that an Alfven winglet develops within Europa's main Alfven wing on that side where the inhomogeneity is located. In addition to the MHD model we apply an analytic model based on the model of Saur et al. (2007) to understand the role of steep gradients and discontinuities in the interaction. We compare our model results with the measured magnetic field data from three flybys of the Galileo spacecraft at Europa which included Alfven wing crossings. Our analysis suggests that the magnetic field might be influenced by atmospheric inhomogeneities during the E26 flyby. The findings of this work will aid in the search for plumes at Europa in future plasma and field observations.